PROFITABILITY MEDIATED EARNING MANAGEMENT AND DETERMINED TAX LOAD MODERATED (Case Study on Registered Manufacturing Company on the Indonesia Stock Exchange 2016-2019 Period) - Ari Pranaditya; Rita Andini; Arditya Dian Andika (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Practice of earnings management is no longer a secret, this phenomenon is carried out as an effort to maintain a managerial performance for the agent against the principal. So that it appears outside the company has the potential to achieve high profits, external parties consider presenting financial statements that are declared good and healthy, but actually the company is in a critical condition. This research aims to analyze the variables that influence the agent's earnings management. Some of the variables that are thought to be able to influence it are; sales growth, leverage, with profitability as a mediating variable, and deferred tax expense as a moderating variable. Population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange for the 2016-2019 period, using a purposive sampling method. In this study, there were 33 who met the criteria, with the number of observations for 4 years (2016-2019), so the number of samples was 132 (33 x 4 years). Vvariable consists of five variables; sales growth, leverage as independent variable, profitability as mediating variable, and deferred tax expense as moderating variable, while earnings management as dependent variable. The data analysis method was carried out by hypothesis testing (t-test), path analysis test (path analysis), and moderating variables using MRA (Moderated Regression Analysis). Research result; Sales growth has a positive and significant effect on profitability, with a sig value of 0.038. Leverege has no positive and significant effect on profitability, with a sig value of 0.095. Sales growth has a positive and significant effect on earnings management, with a sig value of 0.000. Leverege has a positive and significant effect on earnings management, with a sig value of 0.046. Profitability has no positive and significant effect on earnings management, with a sig value of 0.358. Profitability does not mediate the relationship between sales growth and earnings management, direct and indirect effects are greater than indirect effects (0.624 > -0.039). Profitability does not mediate the relationship between leverage and earnings management, direct and indirect effects are greater than indirect effects (0.474 > -0.030). Deferred tax expense strengthens (moderates) the relationship between sales growth and earnings management, the results of the interaction test show the value of sig. of 0.027. Deferred tax expense does not strengthen (moderate) the relationship between leverage and earnings management, the results of the interaction test show the value of sig. of 0.246.